Deformation and Numerical Simulation Analysis of Deep Foundation Pit Excavation of Nanjing Yangtze River Floodplain Metro Station. Issue 3 (April 2021) - Liu, Jiangtao; Nie, Meijun; Li, Cunjun; Yan, Jinpeng
Abstract: Based on the foundation pit excavation construction of a subway station under the soft soil layer of the Nanjing Yangtze River floodplain, Numerical simulation of foundation pit construction process is carried out to study the deformation law of surrounding soil and surrounding structure during foundation pit construction. The research shows that the established finite element numerical model can better predict the structural and stratum deformation caused by the excavation of the foundation pit; the lateral displacement of the ground wall and the ground settlement behind the wall based on different constitutive models are different, but the overall trend is the same. The lateral displacement of the diaphragm wall presents a "bulging" pattern. The surface settlement around the pit shows a settlement trough at a certain distance from the connecting wall. The horizontal displacement of the diaphragm wall increases with the increase of the excavation depth of the foundation pit, and the maximum horizontal displacement occurs above the excavation surface. The conclusions obtained have certain guiding significance for subsequent construction and parameter optimization.